ANALISIS PENGUKURAN BEBAN KERJA FISIK TERHADAP OPERATOR MESIN BORDIR MENGGUNAKAN METODE NORDIC BODY MAP (NBM) DAN METODE RAPID ENTIRE BODY ASSESMENT (REBA) - Resky Gunawan; Nazaruddin; Muhammad Nur; Fitriani Suraya Lubis; Rika Taslim (Indragiri Islamic University, 2025)
This study aims to analyze the physical workload of embroidery machine operators at Elteka Konveksi using the Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA) methods. This method was chosen to identify and evaluate ergonomic risks faced by workers, as well as to provide recommendations for improvements that can increase work comfort and productivity. Data collection was conducted through direct observation and interviews with operators, which aimed to obtain in-depth information about work postures and physical complaints experienced. The results of the analysis show that there are several factors that contribute to high workloads, including unergonomic work postures and long work duration. Based on the evaluation results, it is recommended to make improvements to the workplace design and provide ergonomic training to workers. This research is expected to make a positive contribution to Elteka Konveksi in improving the work system and employee welfare.